EVOLUSI PERAN GURU DARI ERA KONVENSIONAL KE ERA TEKNOLOGI DALAM MENINGKATKAN KEMAJUAN PROSES PEMBELAJARAN - Furmaisuri, Ria; Yulianda, Masnun; Abdurrahmansyah, Abdurrahmansyah; Khadavi Alzafani, Rahmad (CV. Lafadz Jaya, 2025)
The role of teachers in the world of education has undergone significant changes along with the transition from the conventional era to the technological era. In a conventional context, teachers are considered the only source of knowledge, with learning methods that tend to be instructive and focused on teaching from teacher to student. However, technological developments have changed this role, making teachers facilitate, mediators, and innovators in the learning process. With technologies such as e-learning, interactive multimedia, artificial intelligence, and digital platforms, the effectiveness and flexibility of learning have increased, allowing for a more personal and collaborative approach. This transformation requires teachers to develop digital competencies, critical thinking skills, and the ability to adapt to technological advances and the needs of students. The role of teachers is now not only limited to delivering material, but also includes guidance, motivation, and the creation of an innovative and inclusive learning environment. Therefore, the ability of teachers to use technology is very important to improve the quality of education. In improving this progress, there must also be encouragement where in addition to themselves there are also from various parties, including the government and educational institutions, it is very necessary so that teachers can carry out their roles optimally in the digital era, in order to encourage the progress of a more effective and sustainable learning process.